Heterogeneous Selection in a Spatially Structured Environment Affects Fitness Tradeoffs of Plasmid Carriage in Pseudomonads - Slater, Frances R. (American Society for Microbiology (ASM), 2008)
Environmental conditions under which fitness tradeoffs of plasmid carriage are balanced to facilitate plasmid persistence remain elusive. Periodic selection for plasmid-encoded traits due to the spatial and temporal variation typical in most natural environments (such as soil particles, plant leaf and root surfaces, gut linings, and the skin) may play a role. However, quantification of selection pressures and their effects is difficult at a scale relevant to the bacterium in situ. The present work describes a novel experimental system for such fine-scale quantification, with conditions designed to mimic the mosaic of spatially variable selection pressures present in natural surface environments. The effects of uniform and spatially heterogeneous mercuric chloride (HgCl(2)) on the dynamics of a model community of plasmid-carrying, mercury-resistant (Hg(r)) and plasmid-free, mercury-sensitive (Hg(s)) pseudomonads were compared. Hg resulted in an increase in the surface area occupied by, and therefore an increase in the fitness of, Hg(r) bacteria relative to Hg(s) bacteria. Uniform and heterogeneous Hg distributions were demonstrated to result in different community structures by epifluorescence microscopy, with heterogeneous Hg producing spatially variable selection landscapes. The effects of heterogeneous Hg were only apparent at scales of a few hundred micrometers, emphasizing the importance of using appropriate analysis methods to detect effects of environmental heterogeneity on community dynamics. Heterogeneous Hg resulted in negative frequency-dependent selection for Hg(r) cells, suggesting that sporadic selection may facilitate the discontinuous distribution of plasmids through host populations in complex, structured environments.